The Effect of CSR, Information Asymmetry and ROA on Real Earnings Management with Size as a Moderating Factor - Putri Utami Darmawan, Rizky; Christiningrum, MF (Siber Journal of Advanced Multidisciplinary, 2024)
This study examines the effect of CSR, information asymmetry. and ROA on real earnings management with company size as a moderating variable. The sample was selected using purposive random sampling method on manufacturing companies listed on the IDX for the period of 2015-2018. The results show that all variables (CSR, information asymmetry, and ROA) have a signific ant effect on abnormal operating cash flows. However, abnormal operating costs are significantly influenced only by CSR and information asymmetry. Meanwhile, abnormal production costs are significantly influenced by CSR and ROA. The final results show that total real earnings management is influenced by two important factors: Information Asymmetry and ROA. Additionally, the results indicate that company size can moderate the influence of CSR asymmetry and ROA on real earnings management practices. This study contributes to filling the research gap regarding independent factors affecting real earnings management